The Study Of Technical And Operational Performance Of The Transportation Of Grain By Trucks Of The New Generation - Mirzaev N.N., Hamroev R. K. ,Yunusxojaev S.T., Khudoyberdiev M.S. (International Journal of Advanced Science and Technology, 2020)
Recommendations for the use of new-generation trucks with a load capacity of more than 12 tons forgrain transportation were developed, and optimal options for grain transport flows were determined,their technical and operational indicators were determined, based on the operating modes andparameters that ensure high productivity and low side flow.